(untitled) (Research, Society and Development, 2020)
In Brazil, the number of patients with Chronic Kidney Disease remains high. It is estimated that 11 to 22 million individuals manifest some renal dysfunction in a sample of 200 million people. Hemodialysis (HD) appears as renal replacement therapy and offers better quality of life to patients. The aim of the study was to identify the sociodemographic, economic and behavioral profile of chronic renal patients on hemodialysis therapy. This is a quantitative descriptive study that was conducted at the Medical and Statistical Archiving Service (SAME) of a private nephrology clinic in Teresina-PI. The study included patients on hemodialysis treatment older than 18 years and excluded those with infectious diseases or hepatitis C positive serology. The final sample consisted of 174 patients. For data collection, we used a closed questionnaire. Data were entered and organized in Excel spreadsheets and imported into the SPSS version 20.0 program for descriptive analysis. The results showed that 71.8% of patients on hemodialysis treatment were male, 44.2% were over 60 years old, 77.2% incomplete / complete elementary school, 40.2% black, 72.9% married, 79.8% had a catholic religion and 93.1% received a minimum wage. The main pathological antecedents were hypertension, diabetes, glomerunephritis, heart disease, chronic polycystic kidney problems. As for behavioral habits, 54% were sedentary, 33.3% smoker and alcoholic, 21.8% alcoholic and 12.6% smoker. These results are fundamental for the implementation of more effective Health Policies in the prevention of Non-Communicable Chronic Diseases, especially in Chronic Kidney Disease, which has increased significantly in recent years.